An Electric Talempong with Transpose System Based on the Teensy 4.1 Microcontroller - Alfadli Jambak; Riri Jonuarti; Yulkifli; Yohandri (RESSTECH, 2025)
Talempong is a traditional Minangkabau musical instrument that holds significant cultural value and plays a vital role in traditional art performances. However, its application in modern music accompaniment is limited due to a lack of pitch flexibility, as it is generally configured in a fixed base scale such as C=Do. This limitation makes it difficult to integrate talempong into contemporary music arrangements that often require different key scales to suit a singer's vocal range. This research aims to develop an electric talempong equipped with a pitch transposition system based on the Teensy 4.1 microcontroller to enhance its adaptability for modern musical performances. This study employs an engineering approach by designing an electric talempong system using a Teensy 4.1 microcontroller and piezoelectric sensors for 16 pad inputs. Sound frequency is extracted and analyzed using Audacity software. The base pitch is displayed through an OLED screen, while transposition is controlled using two buttons. Testing procedures include sensor characterization, frequency error analysis, accuracy and precision measurement, and practicality evaluation by professional talempong players. The results show that the system has an average frequency error rate of less than 2%, relative accuracy above 97%, and a precision level of up to 99.72% on the C7 note. The practicality score reached 87 out of 100, indicating the system is user-friendly and functional in practice. Therefore, the developed electric talempong proves to be an effective and adaptable instrument for modern music performances while preserving its traditional sound character.